Драматические отрывки и отдельные сцены - Гоголь Николай Васильевич (Пушкинская библиотека, 2000)
Экземпляры: (20181205) / Инвентарный номер: 1802 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Г 58 / ББК: 84(2Рос=Рус)1